2011
DOI: 10.1016/j.immuni.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Selective Utilization of Toll-like Receptor and MyD88 Signaling in B Cells for Enhancement of the Antiviral Germinal Center Response

Abstract: Summary The contribution of Toll-like receptor (TLR) signaling to T cell-dependent (TD) antibody responses was assessed by using mice lacking the TLR signaling adaptor MyD88 in individual cell types. When a soluble TLR9 ligand was used as adjuvant for a protein antigen, MyD88 was required in dendritic cells but not in B cells to enhance the TD antibody response, regardless of the inherent immunogenicity of the antigen. In contrast, a TLR9 ligand contained within a virus-like particle substantially augmented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
251
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(268 citation statements)
references
References 43 publications
(66 reference statements)
15
251
1
1
Order By: Relevance
“…The RNA included in the WIV led to an increase in total IgG levels particularly by increasing levels of IgG2c. This is in accordance with our previous findings that removal of RNA in the VLPs leads to a shift from the IgG2a to the IgG1 isotype [33,34,37]. Importantly, in the publication of Geeraedts et al [36], hemagglutination inhibition (HI) titers follow a similar pattern as total IgG titers in spite of a shift in isotype suggesting that the protective potential of the immune response in this case is dependent of the magnitude of the immune response rather than the isotypes induced.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The RNA included in the WIV led to an increase in total IgG levels particularly by increasing levels of IgG2c. This is in accordance with our previous findings that removal of RNA in the VLPs leads to a shift from the IgG2a to the IgG1 isotype [33,34,37]. Importantly, in the publication of Geeraedts et al [36], hemagglutination inhibition (HI) titers follow a similar pattern as total IgG titers in spite of a shift in isotype suggesting that the protective potential of the immune response in this case is dependent of the magnitude of the immune response rather than the isotypes induced.…”
supporting
confidence: 91%
“…It is important to note that upon assembly of the M2e-AP205 coat protein fusion protein, Escherichia coli RNA is packaged into the VLPs. We have previously shown for VLPs from RNA-phages that removal of the RNA results in a shift of the IgG isotypes induced from IgG2a/c to IgG1 [32][33][34], whereas IgG3 was only marginally affected [33]. Furthermore, presence of RNA also promoted the induction of IgG2b antibodies, which was, however, the subdominant subclass compared with IgG2a/c.…”
Section: Inducing Protective M2e Antibodies By Vaccination: Tlr-signamentioning
confidence: 87%
“…Along this line, Karnowski et al (2012) have recently reported that Pou2af1 −/− CD4 + T cells are not impaired in their ability to differentiate into Tfh cells during influenza infection in mice reconstituted with wild‐type B cells. Viral infections, however, elicit strong Toll‐like receptor signals not only in DCs and B cells, but also in CD4 + T cells that, depending on the pathogenic stimulus and the anatomic compartment, promote the generation of Tfh cells and adaptive immune responses (Hou et al , 2011; Rookhuizen & Defranco, 2014; Kubinak et al , 2015). Based on our observation that Bob can be decisive for CD4 + T‐cell differentiation (Brunner et al , 2007), we analyzed Pou2af1 +/+ : Pou2af1 −/− mixed bone marrow chimeras to determine whether the effects of Bob1‐deficiency on Tfh cell differentiation are CD4 + T cell‐intrinsic or secondary to defects in the B‐cell compartment of Pou2af1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The role of B cell-intrinsic MyD88 signaling has been well studied in virus infection (13)(14)(15)(16) and autoimmunity (20). The stimulation of TLR7 or TLR9 on B cells promotes B cells to produce IgG2 class Abs with decreasing amounts of IgG1 Ab (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Specific deletion of MyD88 in B cells results in defective germinal center (GC) responses and IgG2b and IgG2c production in virus infection or immunization of virus-like particles containing CpG oligodeoxynucleotides, a TLR9 ligand, or ssRNA, a TLR7 ligand (13)(14)(15)(16). Specific involvement of B cell-intrinsic TLR7/9 signaling in IgG2b and IgG2c production is explained by direct upregulation of T-bet in B cells (17,18) and B cell-mediated stimulation of CD4 + T cells to drive IFN-g secretion (16).…”
mentioning
confidence: 99%